Théorie des catastrophes et dynamisme sémantique - Lund, Steffen Nordahl (HERMES - Journal of Language and Communication in Business, 1992)
The article focuses on the potential import of catastrophe theory in the study of word semantics. Thus the lexical content of the French adjective terrible is analyzed within the dynamic geometrical frame-work of the catastrophe theoretic schemata in order to apprehend, on the one hand, the continuum of similar meanings between the two senses (dreadful/formidable) of the word and, on the other hand, the discontinuous reversal between the two opposite values.